2012
DOI: 10.1371/journal.pone.0039601
|View full text |Cite
|
Sign up to set email alerts
|

AID-Targeting and Hypermutation of Non-Immunoglobulin Genes Does Not Correlate with Proximity to Immunoglobulin Genes in Germinal Center B Cells

Abstract: Upon activation, B cells divide, form a germinal center, and express the activation induced deaminase (AID), an enzyme that triggers somatic hypermutation of the variable regions of immunoglobulin (Ig) loci. Recent evidence indicates that at least 25% of expressed genes in germinal center B cells are mutated or deaminated by AID. One of the most deaminated genes, c-Myc , frequently appears as a translocation partner with the Ig heavy chain gene ( Igh ) in mouse pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…hi B cells with high levels of host UNG2 (40). Our data clearly demonstrate an important role for the vUNG in virus replication in the lung that is largely devoid of host UNG, and yet the mechanisms by which the host and viral UNGs contribute to gammaherpesvirus replication are not well characterized.…”
Section: Discussionmentioning
confidence: 75%
“…hi B cells with high levels of host UNG2 (40). Our data clearly demonstrate an important role for the vUNG in virus replication in the lung that is largely devoid of host UNG, and yet the mechanisms by which the host and viral UNGs contribute to gammaherpesvirus replication are not well characterized.…”
Section: Discussionmentioning
confidence: 75%
“…The myc oncogene was not found to be any closer to IgH than other known AID mutated genes in these studies. Based on these observations, the investigators concluded that the proximity of the Ig locus to other genes is not a major determinant in causing AID mutations at non-Ig genes (Gramlich et al 2012).…”
Section: Aid-generated Dna Lesions Can Lead To Chromosomal Instabilitymentioning
confidence: 99%
“…Unlike AID-independent events, the frequency of translocations at hotspots does not correlate with target loci proximity but with the amount of damage inflicted by AID and measured by RPA or Rad51 accumulation during DNA-end resection by homologous recombination (Figure 5A in (Hakim et al, 2012) and Figure 3C in (Yamane et al, 2013), Spearman’s ρ > 0.6). These ideas were independently confirmed in germinal center cells by 3D FISH (Gramlich et al, 2012). In contrast to these studies, Rocha et al reanalyzed our published TC-Seq only from AID +/+ samples and concluded that the frequency of translocations correlates with nuclear proximity (Rocha et al, 2012).…”
mentioning
confidence: 74%